The risk of falls among the aging population: A systematic review and meta-analysis - Xu, Qingmei; Ou, Xuemei; Li, Jinfeng (Frontiers in Public Health, 2022)
Aim This study aims to clarify the risk factors for falls to prevent severe consequences in older adults. Methods We searched the PubMed, Web of Science, Embase, and Google Scholar databases using the terms “risk factors” OR “predicting factors” OR “predictor” AND “fall” OR “drop” to identify all relevant studies and compare their results. The study participants were divided into two groups, the “fall group” and the “control group”, and differences in demographic characteristics, lifestyles, and comorbidities were compared. Results We included 34 articles in the analysis and analyzed 22 factors. Older age, lower education level, polypharmacy, malnutrition, living alone, living in an urban area, smoking, and alcohol consumption increased the risk of falls in the aging population. Additionally, comorbidities such as cardiac disease, hypertension, diabetes, stroke, frailty, previous history of falls, depression, Parkinson's disease, and pain increased the risk of falls. Conclusion Demographic characteristics, comorbidities, and lifestyle factors can influence the risk of falls and should be taken into consideration.